Higher Education in Ethiopia: Recent Developments and Challenges - Yallew, Addisalem (My University, 2020)
This paper explores developments and challenges in Ethiopian higher education focusing on the decade preceding 2018. The article especially focuses on reflecting on issues related to enrolment, staff development, funding, research and graduate studies, internationalization and continuing education.
Keywords: Higher education; enrolment; staff development; funding; research; graduate studies; internationalization; continuing education; Ethiopia